The effect of non-verbal working memory on graphic symbol selection. - Shin, Sangeun; Park, HyunJu (AAC: Augmentative & Alternative Communication, 2022)
To identify the relationship between non-verbal working memory and graphic symbol selection, this study examined whether the response time to select target symbols in a sentence construction task differed between two groups: a high non-verbal working memory group and a low non-verbal working memory group. The interaction effect between non-verbal working memory skills and the degree of exposure to graphic symbols was also examined. Thirty-two non-disabled young adults participated in this study. Based on the quartile of the participants' scores on the non-verbal working memory task (i.e., the backward matrix task), data were selected from the sentence construction task completed by seven participants who belonged to the 25%ile and less and seven who belonged to the 75%ile and more; these data were used to examine group differences. A Mann–Whitney U test showed that non-verbal working memory skills had a significant effect on graphic symbol selection, as the high non-verbal working memory group combined three symbols faster than did the low memory group. No significant interaction effect was found between non-verbal working memory skills and the degree of exposure to symbols. The theoretical and clinical implications of the research findings are discussed.